THE EFFECT OF PROGRAM HEALTH PROMOTION WITH BASIC LIFE SUPPORT SKILLS OF VILLAGE HEALTH VOLUNTEERS SUB-DISTRICT BANG BUA THONG, BANG BUA THONG DISTRICT, NONTHABURI PROVINCE - Sirijittthongchai , Pimradar; Pechmanee , Sarodh; Panyasaisophon , Thanakorn (Primary Health Care Journal (Northeastern Edition), 2024)
Basic life support is important for basic health care of the people, especially village health volunteers who need to have the correct knowledge and skills. This quasi-experimental study aimed to the effect of program applying Pender’s health promotion model with basic life support skills of village health volunteers Sub-District Bang Bua Thong, Bang Bua Thong District, Nonthaburi Province. The samples were divided into two groups. The experimental group consisted of 43 participates group was received a basic life support program and the control group consisted of 43 participates that received regular basic life support program. The simples were selected by simple random sampling. The instruments were applying Pender’s health promotion program questionnaire and skills assessment. Frequencies, percentage, mean, standard deviation, paired samples t-test and independent samples t-test were applied for data analysis. The results of this study were as follows: After receiving the applying Pender’s health promotion program the village health volunteers Sub-District Bang Bua Thong, Bang Bua Thong District, Nonthaburi Province, the experimental group had knowledge basic life support and basic life support skills: patient assessment, chest compressions, and automated external defibrillator (AED) significantly better than before receiving the program and then the control group at < .01 levels. Then, the basic file support program has impact on village health volunteers to have knowledge, understanding and skills in Basic Life Support. The relevant agencies can further develop programs in nearby areas or similar contexts.